CD44 Variant 6 as a Predictive Biomarker for Distant Metastasis in Patients With Epithelial Ovarian Cancer. Issue 6 (June 2016) - Motohara, Takeshi; Fujimoto, Koichi; Tayama, Shingo; Narantuya, Dashdemberel; Sakaguchi, Isao; Tashiro, Hironori; Katabuchi, Hidetaka
Abstract : OBJECTIVE: To investigate the role of cancer stem cell marker CD44 variant 6 in the development of distant metastasis in patients with epithelial ovarian cancer. METHODS: A retrospective cohort study was performed in 186 patients who underwent surgery for ovarian cancer from 2005 to 2013 at the Kumamoto University Hospital. The association between the expression of CD44 variant 6 and distant metastasis was evaluated based on a large-scale immunohistochemical analysis. Primary ovarian tumors that contained at least 10% CD44 variant 6–positive cancer cells were categorized as CD44v6-high (n=53), and the tumors that contained less than 10% CD44 variant 6–positive cells were categorized as CD44v6-low (n=133). Distant metastasis–free survival was compared between the CD44v6-high and -low groups. Multivariate analysis was performed to estimate the influence of various clinicopathologic factors on the development of distant metastasis. RESULTS: At the time of ovarian cancer diagnosis, distant metastasis occurred in 13 of 53 patients (24.5%) in the CD44v6-high group and 17 of 133 patients (12.8%) in the CD44v6-low group ( P =.049). The median metastasis-free survival after stage I–III ovarian cancer diagnosis was 19.5 months (range 11–55 months) in the CD44v6-high group (n=40) and 39.5 months (range 22–57 months) in the CD44v6-low group (n=116) ( P =.071). Multivariate analysis demonstrated that CD44 variant 6 expression was an independent risk factor for distant metastatic recurrence (hazard ratio 4.09, 95% confidence interval 1.29–12.98; P =.017). CONCLUSION: CD44 variant 6 represents an important predictor of distant metastasis and CD44 variant 6–positive ovarian cancer cells play a crucial role in the formation of distant metastases in patients with ovarian cancer. Abstract : Supplemental Digital Content is Available in the Text.CD44 variant 6 is associated with distant metastasis at the time of ovarian cancer diagnosis and is an independent risk factor for recurrence with distant metastasis.